Evaluation of a regionally based preceptorship programme for newly qualified neonatal nurses. Issue 4 (August 2018) - Edwards, Kim; Connett, Gary
Abstract: Introduction: Preceptorship training for newly qualified nurses is well established but practice varies widely. We have introduced and evaluated a regionally based programme for neonatal nurses using novel approaches including use of social media, joint learning with paediatric medical trainees and rotating placements. Methods: A web based questionnaire was developed and given to all preceptees completing the pilot programme. Results: Use of social media and the quality of the programme was highly rated. Logistical issues in relation to providing supernumerary training time, variation in practice across the region and working in a second designated unit were identified. Conclusions: Overall this initiative has been well received. Preceptees completing the programme have become preceptors for successive cohorts joining the programme thus securing long term sustainability.